The Effect of Financial Literacy and Financial Technology on Student Financial Inclusion of Institute of Social Sciences and Management Stiami Jakarta Bekasi Campus - Ismi Amalia Romadhon; Heksawan Rahmadi (Neraca : Jurnal Akuntansi Terapan, 2020)
Financial inclusion is a situation where everyone has access to quality financial services at an affordable cost and a fun way. This research aims to find out the influence of literacy on financial inclusion, to know the influence of financial technolgy on financial inclusion on students of Institute of Social Sciences and Management STIAMI Jakarta Bekasi Campus. The population of this study was a student employee of STIAMI Institute of Social Sciences and Management Jakarta Bekasi Campus and was assigned a sample of 47 respondents, with the method of Simple Random Sampling. The study used questionnaire data collection techniques. Technical analysis of the data used is validity test, reliability, classic assumption, multiple linear, Correlation Coefficient, determination coefficient and hypothesis test. The results of the study based on the t test analysis showed that the financial literacy variable (X1) with a calculated t value of 0.607 > t table 2.01537 or signification 0.547 > 0.05 and variable financial technology (X2) with a calculated value of 3.895 > t table 2.01537 or signification of 0.000 < 0.05, it is said that only financial technology variables (X2) have a significant effect on financial inclusion variables (Y). While the F test results show that independent variables (price and product quality) have a simultaneous influence on dependent variables (purchasing decisions) with a value of F count 10,476 > F table 3.20 or signification of 0.000 < 0.05.. so Ho was rejected and Ha accepted. Based on multiple linear regression analysis the model or equation is Y = 64,392 + 0.095 (X1) + 1,140 (X2).